Biomass-waste derived graphene quantum dots and their applications - Abbas, Aumber (2020)
Energy crisis, environmental deterioration and increasing customer needs have compelled scientists to search facile, low cast, and green routes for the production of novel advanced materials from renewable resources. Among various materials explored, carbon based nanomaterials, especially graphene and graphene quantum dots (GQDs), have attracted extensive attention recently owning to their intriguing properties, such as high conductivity, extensive surface area, good biocompatibility, low toxicity, and long life. This review focuses on the conversion of biomass-waste into GQDs through a number of facile, low cost and scalable routes. Factors affecting the physical and chemical properties of GQDs for numerous promising applications have also been discussed. GQDs have shown promising applications in the field of catalysis, carbon fixation, fuel cells, bio-imaging, drug delivery, and gas sensors. Interestingly, the recent and novel applications of GQDs in the conversion and storage of energy has been discussed here. Finally, the remaining challenges, future perspectives and possible research directions in the field are presented.